OPTIMALISASI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 70% DAUN BINAHONG TERHADAP BAKTERI Staphylococcus aureus - I Putu Gede Adi Purwa Hita; I Putu Riska Ardinata; Zainal Firdaus Wardhana (MEDFARM: Jurnal Farmasi dan Kesehatan, 2023)
Binahong leaf (Anredera cordifolia (Ten.) Steenis) contains flavonoids, alkaloids, tannins and saponins that function as antibacterial. Although antibacterial activity test of binahong leaves was done before, but not yet obtained optimum results using ethanol 70% as an extraction solvent. This study aims to determine the optimum antibacterial activity and the effect of increasing the concentration of 70% ethanolic extract of binahong leaves on Staphylococcus aureus bacteria. Binahong leaves were extracted by maceration method using ethanol 70% as solvent. The antibacterial activity was measured using the disc diffusion method and the inhibition zone obtained was also analyzed using statistical analysis. The results showed that the extract had good extract characteristics and contained a class of flavonoids, alkaloids, saponins, and tannins. The antibacterial activity of the binahong leaf extract showed a significant p-velue <0.05 from the Kruskal Wallis test with an inhibition zone in the moderate to strong group. Based on the results of this study it was concluded that the extract had good extract characteristics and contained several classes of phytochemical compounds. For antibacterial activity, the optimum concentration of antibacterial activity of 70% ethanolic extract of binahong leaves was obtained at an extract concentration of 80% with an inhibition zone was 12.85 mm and it also performed that the higher the concentration of the extract, the higher the antibacterial activity obtained. Keywords: Phytochemical Screening, Antibacterial Activity, Staphylococcus Aureus, Anredera cordifolia (Ten.) Steenis.